Development of a Bioreactor-Based Model for low-density polyethylene (LDPE) Biodegradation by Aspergillus brasiliensis - Daniela Garcia Moreno; Diana Milena Morales Fonseca; Gloria Astrid Nausa Galeano (Universitas Scientiarum)
Low-density polyethylene (LDPE) is a widely used polymer due to its chemical resistance, highflexibility, and mechanical properties. However, its low degradation rate, coupled with its low lifespanand widespread accumulation, poses significant environmental and public health concerns. This studypresents a biodegradation model for LDPE using a suspension bioreactor, which could serve as abiological treatment alternative before polymer disposal. In our model, an initial culture ofAspergillusbrasiliensismetabolized the carbon within the polymer structure and used it as an energy source,leading to LPDE biodegradation and mineralization. The procedure took place in a laboratory-scalebioreactor prototype under aerobic conditions and submerged liquid fermentation. After one month ofculture, a biodegradation percentage of1:89 ̇0:56% was reached. The treated materials were analyzedby scanning electron microscopy (SEM) and fourier transform infrared spectroscopy (FTIR). We foundevidence of biodegradation, colonization of the material, and biofilm formation. This research providespreliminary data on the biodegradation of LDPE under submerged liquid fermentation, marking aninitial phase in the development of a prototype for polymer biodegradation.